Developing a marketing strategy for efficient management of the information environment of the technology park - Mammadov, Javanshir; Huseynov, Yusif; Ahmadova, Metanet; Mammadova, Galiba; Askerov, Arzu (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the managing the information environment of technology parks in Azerbaijan, formed taking into account the competitive specifics of technology parks. Disclosing the problem of high-quality management of the information environment of the technology park requires analyzing the marketing strategy, taking into account the key factors of competition. It is necessary to take into account the key criteria for success and the dominant competitive conditions. The article also presents the main results of a study conducted at the regional universities of Azerbaijan (Sumgait State University and Azerbaijan Technological University) with the aim of developing information and economic mechanisms for the organization and effective operation of technology parks with their further application in the educational environment. Among them: modernization to meet modern requirements; use of marketing tools; adaptation of communication strategy; integration of advanced information technologies; implementation of innovative solutions. In an era of economic growth and dynamism, ideas that seemed like dreams become reality, ahead of their time. Adequate response and application of information technologies in the management of the information environment of the technology park allows to set the direction of the marketing strategy in the new conditions. The study identified three key factors that can have a direct or indirect impact on the organization of an effective consistent approach to the implementation and use of a marketing strategy in the management of a technology park. The obtained results can be used in universities of Azerbaijan, while it is necessary to take into account the key criteria for success and the current competitive conditions